POLITICAL DEVELOPMENT OF LITHUANIA: A COMPARATIVE ANALYSISOF SECONDPOST-COMMUNIST DECADE - Norkus, Zenonas (Politologija, 2015)
The goal of paper is to put into focus and explain essential features of the political development in Lithuania during second post-communist decade by means of its comparison with the analoguos processes in other Baltic States (Latvia and Estonia) and in those Central European countries with political systems which resemble most closely Lithuanian case (Poland and Hungary). In all these countries, second post-communist decade witnessed the rise of the new successful populist parties. The author argues that this populist rise is the proper context for the understanding of Rolandas Paksas’ impeachment in Lithuania in 2003–2004. His Order and Justice party has to be classified together with the brothers Kaczynski’s Law and Justice party and its even more radical allies in Poland, Viktor Orbán’s Fidesz and Gábor Vona’s Jobbik in Hungary, Juhan Part’s Res Publica in Estonia and Einars Repše’s New Era in Latvia. They were all right-wing populist parties, proclaiming in their anti-establishment rhetoric the war on corruption of the (ex-communist) elite and the coming of “new politics”. While the rise of right-wing populism did not change the political system in the former bureaucratic authoritarian countries Estonia and Latvia, in Hungary and Poland the outcome was the breakup of the implicit ex-communist and anti-communist elite pact which was the foundation of the political stability in these former countries of national communism. The Kaczynski twins founded Rzecz Pospolita IV (4th Republic of Poland), grounded in the thorough and comprehensive lustration of the ex-communist cadres. Fidesz leader Victor Orban used the two thirds majority in the Hungarian parliament to promulgate a new constitution. Lithuania is unique in that the ex-communist and anti-communist elite pact was not abolished, but preserved and consolidated due to the collaboration of all, by this time, “established” and Left-of-centre populist parties during the impeachment proceedings. The impeachment of Paksas can be considered as the stress test of the young Lithuanian liberal democracy, just on the eve of the accession of Lithuania to the EU and NATO. An unhappy peculiarity of the stress tests is that they sometimes break or damage the items tested. As far as the success in impeaching R.Paksas prevented the transformation of liberal post-communism into populist post-communism in Lithuania, the test was a success. However, against the expectation of many observers of impeachment events, it did not enhance the quality of democracy of Lithuania. The legacy of impeachment are disequilibrium of the balance of power between government branches in favour of the Constitutional Court, strengthening of the Left-of-Centre populist political forces and the interference of secret services into Lithuanian politics with the self-assumed mission to safeguard Lithuanian democracy from the perils of populism.